Contents, Contributors and Introduction, LTC - volume 20 - Ann Genovese; Shaun McVeigh; Peter D. Rush (Law Text Culture, 2016)
This collection of essays for Law Text Culture is a collaboration and meditation on methods and genres of life writing, and how they might be adequate to the task of taking responsibility for legal thought and lawful relations as lived in Australia today. In many ways, these essays, and what they represent together, could be described as Legal Biographies. For a very long time, Legal Biographies have been written to animate the study of the common law and its institutions through lives of jurists and judges.